Unidentified Language Deficits in Children with Emotional and Behavioral Disorders: A Meta-Analysis. (January 2014) - Hollo, Alexandra; Wehby, Joseph H.; Oliver, Regina M.
Low language proficiency and problem behavior often co-occur, yet language deficits are likely to be overlooked in children with emotional and behavioral disorders (EBD). Random effects meta-analyses were conducted to determine prevalence and severity of the problem. Across 22 studies, participants included 1, 171 children ages 5–13 with formally identified EBD and no history of developmental, neurological, or language disorders. Results indicated prevalence of below-average language performance was 81%, 95% CI [76, 84]. The mean comprehensive language score was 76.33 [71, 82], which was significantly below average. Implications include the need to (a) require language screening for all students with EBD, (b) clarify the relationship between language and behavior, and (c) develop interventions to ameliorate the effects of these dual deficits.